Evaluation Of Pandanus Amaryllfolius Leaves Extract As Eco-Friendly Corrosion Inhibitor Of Mild Steel In Hydrchloric Acid Solution - Asri, Nur Allia (Universiti Sains Malaysia, 2018)
Corrosion of metal has been a great deal in industry as well as life application concerning its impact on human life and safety, economics and environment. The study was done to evaluate the potential of Pandanus amaryllfolius extract as corrosion inhibitor for mild steel in hydrochloric acid (HCl) solution. In this study, the inhibition ability of m P.amaryllfolius extract on mild steel in 1.0 M hydrochloric acid (HCl) was evaluated at different concentration of P.amaryllfolius extract (0.2-1.0 g/L) and temperature (30-70˚C) of acidic medium with addition of P.amaryllfolius extract. Mild steel coupon was immersed in uninhibited and inhibited HCl medium for 24 hours and corrosion rate was calculated using weight loss method. Inhibition ability of the P.amaryllfolius extract was found to increase with increasing concentration with optimum inhibition ability at concentration 0.6 g/L extract in 1.0 M of HCl with efficiency of 98.24% at ambient temperature. However, the inhibition ability of the extract was decreasing with increasing temperature. The adsorption isotherm of the inhibiting compound in the P.amaryllfolius extract on mild steel surface was studied and the isotherm plotted matches with Langmuir isotherm. The adsorption constant, Kads calculated from Langmuir isotherm is 0.1177 L/g indicates the adsorption of P.amaryllfolius extract to the metal surface. Enthalpy, ∆H of uninhibited and inhibited system calculated are 31.345 kJ/mol and 92.305 kJ/mol, respectively shows that the reaction is endothermic. Entropy ∆S calculated for inhibited and uninhibited system are -43.423 kJ/mol and -124.91 kJ/mol respectively. From the parameters calculated, ∆G obtained from the studies is -11.81kJ/mol showing that physisorption process takes place to halt the corrosion reaction of mild steel. The protective film of inhibiting compound formed on mild steel surface was studied using Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC-MS). It was found from the results that the compound responsible for inhibiting ability of P.amaryllfolius extract are those with hydroxyl functional group.